Die Parasiten der paläarktischen Yponomeutidae (Lepidoptera, Hymenoptera, Diptera). - Friese, Gerrit (Contributions to Entomology = Beiträge zur Entomologie, 1963)
There are summarized the hitherto known parasites (Hymenoptera and Diptera) of palearctic Yponomeutidae.